1996
DOI: 10.1093/hmg/5.11.1809
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the pancreatic islet inward rectifier Kir6.2 also leads to familial persistent hyperinsulinemic hypoglycemia of infancy

Abstract: Closure of ATP-sensitive potassium channels in pancreatic islet beta-cells initiates a cascade of events that leads to insulin secretion. beta-Cell ATP-sensitive potassium currents can be reconstituted by coexpression of the inward rectifier Kir6.2 and the sulfonylurea receptor (SUR), a member of the ATP-binding cassette superfamily. Mutations in SUR have been identified in individuals affected with familial persistent hyper-insulinemic hypoglycemia of infancy (PHHI), an autosomal recessive disorder of glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
229
0
5

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(234 citation statements)
references
References 22 publications
0
229
0
5
Order By: Relevance
“…In the absence of clinical treatment, PHHI may be lethal or result in irreversible neurologic sequelae. To date, three mutations responsible for PHHI have been identified in the Kir6.2 gene (21)(22)(23) and in numerous mutations in the SUR1 gene (1, 24 -30). Some of the SUR1 mutations are nonsense or frameshift mutations that produce a truncated form of SUR1.…”
Section: Atp-sensitive Potassium (K Atpmentioning
confidence: 99%
“…In the absence of clinical treatment, PHHI may be lethal or result in irreversible neurologic sequelae. To date, three mutations responsible for PHHI have been identified in the Kir6.2 gene (21)(22)(23) and in numerous mutations in the SUR1 gene (1, 24 -30). Some of the SUR1 mutations are nonsense or frameshift mutations that produce a truncated form of SUR1.…”
Section: Atp-sensitive Potassium (K Atpmentioning
confidence: 99%
“…Loss of function of the pancreatic islet K ATP channel, because of mutation of either the SUR1 or Kir6.2 subunit (11)(12)(13)(14), has been demonstrated to lead to persistent hyperinsulinemic hypoglycemia of infancy, an autosomal recessive disorder characterized by unregulated insulin secretion and severe hypoglycemia (15). Disease phenotypes have not yet been assigned to the other K ATP channels.…”
Section: Atp-sensitive Potassium (K Atp )mentioning
confidence: 99%
“…Rare mutations in KCNJ11 14 can lead to neonatal diabetes and hyperinsulinaemia of infancy (depending on the direction of their effect on channel function). 15 Previous comprehensive tagging studies have demonstrated that common variation within the single exon of KCNJ11, in particular the E23K variant (which is in almost complete LD (40.9) with the A1369S variant within the neighbouring ABCC8 but with no other nonsynonymous variants in KCNJ11), is heavily implicated in susceptibility to multifactorial T2D. 16 Furthermore, E23K is the polymorphism within KCNJ11 most likely to be aetiological for T2D, on both statistical and functional grounds.…”
Section: Introductionmentioning
confidence: 99%